1997
DOI: 10.1073/pnas.94.24.13357
|View full text |Cite
|
Sign up to set email alerts
|

Phytosulfokine-α, a sulfated pentapeptide, stimulates the proliferation of rice cells by means of specific high- and low-affinity binding sites

Abstract: Peptide growth factors were isolated from conditioned medium derived from rice (Oryza sativa L.) suspension cultures and identified to be a sulfated pentapeptide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
77
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(91 citation statements)
references
References 28 publications
4
77
1
2
Order By: Relevance
“…The only protoplast cultures, which have been shown to respond to PSK with enhanced proliferation activity, were derived from cell suspensions of rice (Matsubayashi et al 1997). In this paper we report a very high positive impact of PSK on otherwise extremely recalcitrant sugar beet leaf protoplast culture.…”
Section: Introductionmentioning
confidence: 68%
“…The only protoplast cultures, which have been shown to respond to PSK with enhanced proliferation activity, were derived from cell suspensions of rice (Matsubayashi et al 1997). In this paper we report a very high positive impact of PSK on otherwise extremely recalcitrant sugar beet leaf protoplast culture.…”
Section: Introductionmentioning
confidence: 68%
“…Subsequent studies demonstrated the existence of PSK-K in CM derived from both monocot [7] and dicot [8,9] cell cultures. Furthermore, isolation of a rice (Oryza sativa L.) cDNA, OsPSK, encoding a putative PSK-K precursor has been achieved [10] and it was also shown that rice suspension cells contain both speci¢c high-and low-a¤n-ity saturable PSK-K binding sites on their plasma membranes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the most important are growth regulators, particularly auxins and cytokinins, normally essential for sustained divisions of protoplast-derived cells and their further differentiation into plants (Davey et al 2005b). Recently, oligopeptides have been recognized as signaling molecules playing an important role in plant cell growth and development (Matsubayashi et al 1997;Ryan and Pearce 2001). One of them is phytosulfokine (PSK), a plant-specific disulfated pentapeptide isolated for the first time from conditioned medium of an Asparagus officinalis mesophyll cell culture (Matsubayashi and Sakagami 1996).…”
Section: Introductionmentioning
confidence: 99%